(untitled) (Perioperaciina Medicina, 2024)
Background. Degenerative-dystrophic diseases of the joints are chronic progressive pathological conditions, accompanied by such features as presence of pain syndrome, impaired functional capacity, muscle weakness, deformation and instability of the joints. The high prevalence of degenerative-dystrophic diseases of the hip joint necessitates the search for optimal non-invasive treatment methods. Objectives. This study aims to analyze the clinical results of intra-articular injections of hyaluronic acid solution (Diart) in the treatment of patients with II–III stages of degenerative-dystrophic diseases of the hip joint. Materials and methods. The clinical results of 30 patients with II–III stages of degenerative-dystrophic diseases of the hip joint were analyzed. The group included 11 (36.67%) males and 19 (63.33%) females. The mean age of group was 61.43±7.98 years. All patients underwent a course of drug therapy using hyaluronic acid solution (Diart), which included 3 intra-articular injections of the drug, which were performed with the 7-day interval. Clinical results were evaluated at the initial visit, at 7, 14, 30 and 90 days after the first injection of Diart by objective examination of patients and analysis of subjective data using the WOMAC questionnaire. Statistical analysis was performed using Statistica 13 software package. Results. The high effectiveness of intra-articular injections of hyaluronic acid (Diart) in the treatment of patients with II-III stages of degenerative-dystrophic diseases of the hip joint and the absence of complications associated with intra-articular injection of the drug have been established. Signs of post-injection sy- novitis, discomfort, swelling or other unpleasant sensations weren’t observed in any of the examined patients. Comparing the results established during remote period, on the 90th day of observation, and indicators determined at the initial visit, we proved a decrease in the intensity of the pain syndrome in the hip joint by 30.35%, in stiffness — by 29.57%, an improvement in the indicators characterizing the functional capacity by 21.34 % and the total values of the WOMAC index — by 27.37%, after a treatment course using Diart. Conclusion. The high efficiency of using intra-articular injections of hyaluronic acid solution (Diart) in the treatment of patients with II–III stages of degen- erative-dystrophic diseases of the hip joint has been proven.